Komunikasi Politik Kontestan Pilkada Jawa Tengah 2018 - Fathan .; Abraham Zakky Zulhazmi (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2019)
Mass media has an influence on society in taking the decision. The use of language structure presents their identity from the media. Finally, the language is understood as a room where conflict of importance, strength, and hegemony process and counter-hegemony happened. The research is going to analyze the mass media politic language on the governor election in Central Java 2018. The method is discourse analysis by Halliday and Hasan. The model refers to the situation context includes three components: (1) field of discourse; (2) tenor of discourse; (3) mode of discourse. The analyzed news is the news of the Central Java governor election debate. The conclusion is both media consider the Central Java governor election in 2018 is less interesting. Besides, Suara Merdeka and Solopos appreciate that the Central Java governor election in 2018 as a well-mannered debate, it could be seen from the diction of the news. Media massa memiliki pengaruh yang kuat bagi khalayak dalam mengambil keputusan. Penggunaan struktur Bahasa media merepresentasikan jati diri dari media tersebut.Bahasa pada akhirnya dipahami sebagai sebuah ruang dimana konflik kepentingan, kekuatan, proses hegemoni dan counter-hegemony terjadi.Penelitian ini ingin menganalisis bahasa komunikasi politik media massa pada pemilihan gubernur Jawa Tengah tahun 2018. Metode penelitian ini menggunakan analisis wacana model Halliday dan Hasan. Model ini mengacu pada konteks situasi yang meliputi tiga komponen, yaitu: (1) Medan Wacana (field of discourse); (2) Pelibat Wacana (tenor of discourse); (3) Sarana Wacana (mode of discourse). Berita yang dianalisis adalah berita tentang debat pemilihan kepala daerah Jawa Tengah. Kesimpulan penelitian ini adalah kedua media sama-sama menganggap pemilihan gubernur Jawa Tengah 2018 kurang menarik. Selain itu Suara Merdeka dan Solopos juga menilai debat pemilihan gubernur Jawa Tengah 2018 sebagai debat yang santun, terlihat dari pilihan kata yang digunakan dalam pemberitaan.